IMPLEMENTATION OF MANAGEMENT INFORMATION SYSTEMS IN THE DECISION-MAKING PROCESS AT CHATIME - Grace Sri Naomika Ginting; Nazwa Atikah PH; Ryndian Gusty; Indra Siregar; Dewi Comala Sari (CV. Visionary Raya Sakti, 2026)
Management Information Systems (MIS) are strategic components used by companies to process data and generate information as a basis for decision-making. In the ready-to-drink beverage industry, the implementation of MIS plays a role in ensuring operational effectiveness, consistency in quality standards, and accuracy in marketing strategies. This study aims to analyze the implementation of MIS in supporting decision-making at the Chatime Setiabudhi outlet. The research uses a descriptive qualitative method through in-depth interviews with outlet employees. The results show that MIS is implemented in an integrated cashier system, inventory management, SOP-based employee training system, and customer data-based marketing strategies. MIS has improved operational efficiency, accelerated communication between outlets and headquarters, and strengthened decision-making related to sales, inventory, and customer service. The obstacles found include supply delays and system malfunctions, but these can be overcome through headquarters support and backup procedures. This study concludes that the effectiveness of MIS is influenced by system integration, human resource competence, and consistency in implementing SOPs.